Tourist-virtual assistant communication: the power of attachment and authenticity - Ferreira, Mónica Mendes; Pereira, H.; Ashfaq, M.; Loureiro, S. M. C. (Anatolia, 2023)
This study analyses tourist-virtual assistant communication by demonstrating the effect of authenticity and attachment as drivers of engagement. A Qualtrics panel sample of 200 users of intelligent virtual assistants (IVA) for the purpose of tourism was recruited to fulfil a survey. Findings show that when users view their communication with IVA as authentic, they become engaged. Yet, the strength of the relationship between attachment and engagement tends to be higher than the relationship between authenticity and engagement. Prominence is more important in creating attachment than self-connection. Tourists who are closer to their IVA, thinking, feeling, and using it to interact with brands are also more related to the information and recommendations given by the IVA and establish a stronger interaction.